Akad Perbankan Syariah dan Penerapannya dalam Akta Notaris Menurut Undang-Undang Jabatan Notaris - Pandam Nurwulan (Jurnal Hukum IUS QUIA IUSTUM, 2018)
This study examines, first, why the binding guarantee in Shariah banking deed still practice the concept used by conventional banking. Second, how the notary formulates Sharia banking deeds in accordance with Law on Notary, and third, the ideal requirements for a notary in formalizing Sharia banking deeds. The research method used is normative legal research by processing and analyzing data in a qualitativedescriptive approach. The results show that, first, the binding guarantee of Sharia banking deeds still uses  the  concept  of  conventional  banking  guarantee because  there  are  no  Sharia  rules/regulations governing a matter of binding guarantee for Sharia deeds (there is a legal vacuum/recht vacuum). As a result,  the  practice  of  guarantee  binding  procedures  for  Sharia  banking  deeds  uses  mortgage  and fiduciary  rights  as  is  commonly  practiced  by  conventional  banking.  Secondly,  in  formulating  Sharia deeds,  a  notary  should  follow  the  Law  on  Notary  without  leaving  the  Sharia  principles  and mechanism/procedure for making a Notary deed. Third, the notary inaugurating Sharia deeds must be well acquainted with Sharia principles, which are based on the divinity principle in Sharia deeds, making it ideal if the notary who legalizes the Sharia deeds is a Muslim.